Menggambar Animasi Dalam Tinjauan Kaidah Al Ashlu Fi Asyai Al Ibaha - Karlin Permata Suri (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2023)
Images that can move and look real are known as animation which is currently not only enjoyed by children as a form of learning while playing, but animation has also become entertainment for teenagers and adults. In the early days of Islam, drawing was an act that was prohibited because pictures were made for the purpose of being revered and they were often worshiped. This of course can affect people who have just embraced Islam because it can affect their firmness in believing that Islam is the true religion, because this is a habit that they often do when they are not yet a Muslim. This continues to be believed by the Muslim community as an act that is prohibited in Islam until today's modern times. This research focuses on the act of drawing animation in terms of the fiqh rules of al-Ashlu fi Asyai al-Ibaha with the formulation, First, why is drawing still referred to as an unlawful act in modern times. The second is how the rule of al-Ashlu fi asyai al ibahah is applied in the problem of drawing animation in today's modern times. The results of this study are, First, the act of drawing was prohibited at the beginning of the Islamic period which caused it to continue to be believed today because it was feared that the images made would be used to worship or get blessings from people they believed were holy, which of course this was acts that associate partners with Allah SWT. Second, the rule of al-Ashlu fi asyai al-Ibahah is a rule that can be applied to this act of drawing, bearing in mind that drawing at this time has a lot of benefits arising from its harm such as entertainment, education, business and others, so it needs to be understood that drawing is basically an act that is permissible as long as it does not lead to things that are forbidden..